The Effect of Capital Intensity, Profitability, and Inventory Intensity on Tax Avoidance - Firliana, Birnika Pristanila; Yanto (Accounting Study Program, Faculty of Economics and Business, 2024)
This study analyzes the effect of capital intensity, profitability, and inventory intensity on tax avoidance practices in oil and gas companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Using secondary data from financial statements and purposive sampling technique, 41 samples were obtained to be analyzed through multiple linear regression using SPSS. The results show that capital intensity has a significant negative effect on tax avoidance, which means that the higher the asset intensity, the lower the company's tendency to avoid taxes. In contrast, profitability and inventory intensity have no significant effect on tax avoidance. These findings provide important insights into the factors that influence corporate tax behavior in the oil and gas sector., offering valuable input for policymakers and company management to design strategies promoting tax compliance. This study also highlights the importance of examining specific financial characteristics to understand tax avoidance practices better, emphasizing the role of asset allocation and its implications for corporate tax strategies.